2011
DOI: 10.3390/ijms12117286
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Fibers Modified with HAp/β–TCP Nanoparticles

Abstract: This paper describes a method for preparing chitosan fibers modified with hydroxyapatite (HAp), tricalcium phosphate (β-TCP), and HAp/β-TCP nanoparticles. Fiber-grade chitosan derived from the northern shrimp (Pandalus borealis) and nanoparticles of tricalcium phosphate (β-TCP) and hydroxyapatite (HAp) suspended in a diluted chitosan solution were used in the investigation. Diluted chitosan solution containing nanoparticles of Hap/β-TCP was introduced to a 5.16 wt% solution of chitosan in 3.0 wt% acetic acid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…This calcium phosphate is easily identified by presenting a broad band in 900-1200 cm -1 ; observed the presence of the peak at 724 cm -1 , characteristic of the symmetric mode (P-O-P) assigned to distortion of P-O. Since the peak at 1211 cm -1 is characteristic of a non-degenerate deformation of hydrogen groups -OPO 3 , -H, O-PO 3 , common ions HPO 4 -2 , the presence of this group may be a consequence of the interaction of water molecules in the structure [18][19][20][21] (Figure 2). …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This calcium phosphate is easily identified by presenting a broad band in 900-1200 cm -1 ; observed the presence of the peak at 724 cm -1 , characteristic of the symmetric mode (P-O-P) assigned to distortion of P-O. Since the peak at 1211 cm -1 is characteristic of a non-degenerate deformation of hydrogen groups -OPO 3 , -H, O-PO 3 , common ions HPO 4 -2 , the presence of this group may be a consequence of the interaction of water molecules in the structure [18][19][20][21] (Figure 2). …”
Section: Resultsmentioning
confidence: 96%
“…Chitosan/ß-TCP/HAp complex solution was prepared according to a method elaborated in the Institute of Biopolymers and Chemical Fibers, Poland [17,18].…”
Section: Preparation Of Hydrochloric Chitosan/ ß-Tcp and Hap Complex mentioning
confidence: 99%
“…Grain size fits mainly in the range 1.0 -10.0 μm, average particle size of HAp is 3.24 ± 0.81 µm, also according with the literature [15] …”
Section: Analysis Of the Particles Size Of The Hydroxyapatitementioning
confidence: 92%
“…The SEM analysis showed a HAp great ability to agglomeration and cluster formation, the small particles tend to agglomerate due to the increased intensity of the attractive forces on the repulsive, because the charge distribution on the surfaces and the water adsorption [15] [19] [25]. Samples 10 and 11 were chosen for further studies because shown the best structure and the highest content of calcium phosphates of the set of samples according with Table 1.…”
Section: Sem Study Of the Filmsmentioning
confidence: 99%
See 1 more Smart Citation